PENGARUH KUALITAS PRODUK, HARGA PRODUK, DAN CITRA MEREK TERHADAP MINAT PEMBELIAN PRODUK MAHLIGAI ANYAM - Arini, Arini; Saputra, Sahrul; Manalu, Doresly Handayanti; Bakti, Siti Meyla (Jurnal Ekonomi Bisnis Kompetif, 2025)
This study aims to determine the influence of product quality, product price, and brand image on the purchase intention of Mahligai Anyam products. The background of this research lies in the intense competition within the local handicraft industry, which requires businesses to enhance product quality, set competitive prices, and build a strong brand image to attract consumer interest. This research employs a quantitative approach using the survey method. Data were collected through questionnaires distributed to 125 consumers who have purchased Mahligai Anyam products. The data were analyzed using multiple linear regression analysis to examine the effect of each independent variable on the dependent variable. The results show that product quality, product price, and brand image have a positive and significant effect on the purchase intention of Mahligai Anyam products. This indicates that the better the quality and brand image offered, and the more appropriate the product price is to the perceived value, the higher the consumers’ purchase intention will be. These findings are expected to serve as input for Mahligai Anyam in formulating effective marketing strategies to enhance competitiveness and sales performance.